2004
DOI: 10.1038/sj.onc.1208236
|View full text |Cite
|
Sign up to set email alerts
|

REDD1 integrates hypoxia-mediated survival signaling downstream of phosphatidylinositol 3-kinase

Abstract: Cancer cells frequently evade apoptosis during tumorigenesis by acquiring mutations in apoptotic regulators. Chronic activation of the PI 3-kinase-Akt pathway through loss of the tumor suppressor PTEN is one mechanism by which these cells can gain increased protection against apoptosis. We report here that REDD1 (RTP801) can act as a transcriptional downstream target of PI 3-kinase signaling in human prostate cancer cells (PC-3). REDD1 expression is markedly reduced in PC-3 cells treated with LY294002 (LY) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 58 publications
11
108
2
Order By: Relevance
“…On the other hand, REDD1 was found to play an important role in the growth of prostate cancer cells (PC-3) in vitro and in vivo reported by Schwarzer et al Reduced REDD1 levels could sensitize cells to apoptosis, whereas elevated levels of REDD1 induced by hypoxia or overexpression desensitized cells to apoptotic stimuli. 13 It was also shown in another study that mice with the BRCA1 mutation and p53 haploid loss exhibited increased expression of REDD1 and had high cancer susceptibility. 14 As reported by An SJ and colleagues, REDD1 also was found to be overexpressed in carcinoma induced by BPDE-transformed 16HBE cells (16HBE-C cells).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, REDD1 was found to play an important role in the growth of prostate cancer cells (PC-3) in vitro and in vivo reported by Schwarzer et al Reduced REDD1 levels could sensitize cells to apoptosis, whereas elevated levels of REDD1 induced by hypoxia or overexpression desensitized cells to apoptotic stimuli. 13 It was also shown in another study that mice with the BRCA1 mutation and p53 haploid loss exhibited increased expression of REDD1 and had high cancer susceptibility. 14 As reported by An SJ and colleagues, REDD1 also was found to be overexpressed in carcinoma induced by BPDE-transformed 16HBE cells (16HBE-C cells).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, DDIT4 function appears to be context-dependent. In some cancer cell lines and mouse models, DDIT4 appears to act as an oncogene in a prosurvival role in part by blocking apoptosis (71,72), whereas in other cell-based and in vivo experiments, it functions as a tumor suppressor (67,73). When considering whether HUWE1 is an appropriate target for cancer or other disease indications, it should be noted that inhibition of HUWE1 with a concomitant increase in DDIT4 expression may have beneficial or detrimental effects for the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypoxic induction, REDD-1 can be induced by either ATP depletion or direct activation of the AMP-activated protein kinase (AMPK). These studies have shown that REDD-1 is a critical transducer of the cellular response to energy depletion and hypoxia through the mTOR pathway (Fig 3) [27][28][29].…”
Section: Other Sensors Of Metabolic Stressmentioning
confidence: 99%